"Hand Surgeons Probably don't Starve": Patient's Perceptions of Physician Reimbursements for Performing an Open Carpal Tunnel Release. (December 2015) - Kokko, Kyle P.; Lipman, Adam J.; Sapienza, Anthony; Capo, John T.; Barfield, William R.; Paksima, Nader
Background: The purpose of this study is to evaluate patient's perceptions of physician reimbursement for the most commonly performed surgery on the hand, a carpal tunnel release (CTR). Methods: Anonymous physician reimbursement surveys were given to patients and non-patients in the waiting rooms of orthopaedic hand physicians' offices and certified hand therapist's offices. The survey consisted of 13 questions. Respondents were asked (1) what they thought a surgeon should be paid to perform a carpal tunnel release, (2) to estimate how much Medicare reimburses the surgeon, and (3) about how health care dollars should be divided among the surgeon, the anesthesiologist, and the hospital or surgery center. Descriptive subject data included age, gender, income, educational background, and insurance type. Results: Patients thought that hand surgeons should receive 5030 for performing a CTR and the percentage of health care funds should be distributed primarily to the hand surgeon (56 %), followed by the anesthesiologist (23 %) and then the hospital/surgery center (21 %). They estimated that Medicare reimburses the hand surgeon 2685 for a CTR. Most patients (86 %) stated that Medicare reimbursement was "lower" or "much lower" than what it should be. Conclusion: Respondents believed that hand surgeons should be reimbursed greater than 12 times the Medicare reimbursement rate of approximately 412 and that the physicians (surgeons and anesthesiologist) should command most of the health care funds allocated to this treatment. This study highlights the discrepancy between patient's perceptions and actual physician reimbursement as it relates to federal health care. Efforts should be made to educate patients on this discrepancy.